2019
DOI: 10.1155/2019/9648761
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Secondhand Tobacco Smoke at Airport Terminals

Abstract: Background. Airports may represent significant sources of secondhand smoke (SHS) exposure for both travelers and employees. While previously common smoking rooms have largely disappeared from US airports, smoking continues to occur outdoors at terminal entrances. SHS may be especially high at arrival areas, since they oftentimes are partially enclosed by overhead departures, creating stagnant microenvironments. This study assessed particulate matter <2.5 microns in diameter (PM2.5), a common surrogate for S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…The high levels of secondhand smoke (SHS) in and adjacent to DSR show that these rooms are not providing safe air quality for employees and travelers 6 . A study in 2010 found that PM2.5 which is a common measure of SHS, leaked from enclosed airport smoking venues and entered the general air circulation which exposed the workers and the public to SHS 7 . The average PM2.5 concentrations inside the smoking rooms were notably higher than the National Ambient Air Quality Standard for 24 hours (35 μg/m 3 ) 8 .…”
mentioning
confidence: 99%
“…The high levels of secondhand smoke (SHS) in and adjacent to DSR show that these rooms are not providing safe air quality for employees and travelers 6 . A study in 2010 found that PM2.5 which is a common measure of SHS, leaked from enclosed airport smoking venues and entered the general air circulation which exposed the workers and the public to SHS 7 . The average PM2.5 concentrations inside the smoking rooms were notably higher than the National Ambient Air Quality Standard for 24 hours (35 μg/m 3 ) 8 .…”
mentioning
confidence: 99%